Early Prototype Assessment of a New Virtual System for Training Procedural Skills of Automotive Service Operators: LARTE Tool - Borsci, Simone; Lawson, Glyn; Burgess, Mark; Jha, Bhavna (Human-Computer Interaction: Users and Contexts, 2015)
The consortium of the Innovate UK funded Live Augmented Reality Training Environments (LARTE) project, composed of Jaguar Land Rover (JLR), Holovis International Ltd and The University of Nottingham, developed a new concept of a 3D multiplatform training system to train the procedural skills of service maintenance operators. The LARTE tool was designed on the basis of JLR needs and desiderata. This paper presents the functionalities of the initial prototype of LARTE training system, and outcomes of an evaluation study of the usability of the product.